Implementation Of Coopertive Learning Strategies To Improve Learning Outcomes In Subjects Of Civic Education Main Subjects State Power Sharing System Of 10th Grade Students Accounting In SMKN Tanimbar Selatan - Sabarlele, Veky Robinson (Global Science Education Journal, 2019)
The purpose of this classroom action research (CAR) is to aim to find out whether there is an increase in learning outcomes in the subject of Citizenship Education students using cooperative learning strategies. This research is a classroom action research study involving 30 students of class X Accounting SMKN 2 Tanimbar Selatan consisting of 5 women and 20 men. Some of the variables investigated in this study are as follows (1) input variables which include students, lesson material, learning resources, (2) the variable process of organizing teaching and learning activities, such as teaching and learning interactions, student questioning skills, student learning methods, and (3) output variables such as student curiosity, students' ability to apply knowledge, student learning motivation, student learning outcomes, student attitudes towards learning experiences through improvement activities. There are four stages carried out in carrying out this research activity, namely: the stages of planning, implementation of actions, observation and interpretation as well as analysis and reflection. This research was conducted in two research cycles. From the results of the action in the first cycle, it was found that the average value of students was 78.67 with the highest score of 90 and the lowest value of 65 and completeness of learning only reached 77% or 23 students out of 30 students, still below the established completeness of 85% of students unfinished learning 23% or 7 students out of 30 students. Thus the next learning cycle still needs to be designed. Results in Cycle II the average value of students 81.00 with the highest value of 95 and the lowest value of 70 and completeness of learning has only reached 87% or 26 students out of 30 students, already above the mastery that has been set that is 85% of students who have not finished learning 13 % or 4 students out of 30 students. Thus there is no need to design further learning cycles. The results showed that the use of cooperative learning strategies in fact can improve learning outcomes in subjects Citizenship Education in class X Accounting for SMKN 2 Tanimbar Selatan 2018/2019